Exploring Differentiated Instruction in College English Teaching in the Context of ChatGPT - Zhang, Lingli (Pacific International Journal, 2025)
The rapid development of artificial intelligence technology has brought new opportunities and challenges to the field of education. As a large language model, ChatGPT has demonstrated powerful capabilities in language understanding and generation, providing new possibilities for differentiated instruction of college English. This paper aims to explore the paths of differentiated instruction of college English in the context of ChatGPT, analyze its advantages and challenges, and propose corresponding teaching strategies. The research adopts the literature research method and case analysis method. By analyzing the technical characteristics of ChatGPT and its educational application scenarios, it explores the differentiated instruction of college English based on ChatGPT. The research shows that ChatGPT can effectively support the differentiated instruction of college English, enhance students’ learning interest and learning effectiveness, but there are also challenges in terms of data security, ethics, and other aspects.